Hepatitis C virus–induced CCL5 secretion from macrophages activates hepatic stellate cells. Issue 3 (18th July 2017) - Sasaki, Reina; Devhare, Pradip B.; Steele, Robert; Ray, Ranjit; Ray, Ratna B.
Abstract : Hepatitis C virus (HCV)–mediated chronic liver disease is a serious health problem around the world and often causes fibrosis/cirrhosis and hepatocellular carcinoma. The mechanism of liver disease progression during HCV infection is still unclear, although inflammation is believed to be an important player in disease pathogenesis. We previously reported that macrophages including Kupffer cells exposed to HCV induce proinflammatory cytokines. These secreted cytokines may activate hepatic stellate cells (HSCs) toward fibrosis. In this study, we examined crosstalk between macrophages and HSCs following HCV infection. Primary human HSCs and immortalized HSCs (LX2 cells) were incubated with conditioned medium derived from HCV‐exposed human macrophages. Expression of inflammasome and fibrosis‐related genes in these cells was examined, with increased expression of inflammatory (NLR family pyrin domain containing 3, interleukins 1β and 6, and cysteine‐cysteine chemokine ligand 5 [CCL5]) and profibrogenic (transforming growth factor β1, collagen type 4 alpha 1, matrix metalloproteinase 2, and alpha‐smooth muscle actin) markers. Further investigation suggested that CCL5, secreted from HCV‐exposed macrophages, activates inflammasome and fibrosis markers in HSCs and that neutralizing antibody to CCL5 inhibited activation. Conclusion : Together, our results demonstrate that human macrophages exposed to HCV induce CCL5 secretion, which plays a significant role in hepatic inflammation and fibrosis. (Hepatology 2017;66:746–757).